Виключність як властивість рішення суду у цивільній справі, що набрало законної сили - Гаврік Роман Олександрович (Науковий вісник Державної прикордонної служби України. Серія Юридичні науки, 2015)
У зазначеній науковій статті проведене наукове дослідження юридичних особливостей виключності судових рішень, ухвалених у справах окремого провадження, що набрали законної сили. Зокрема, визначено поняття виключності рішення суду у справі окремого провадження, її правові наслідки. Виділені критерії визнання вимоги у справі про встановлення юридичного факту у окремому або позовному провадженні тотожною, тобто такою, що не може бути повторно розглянута у цивільному процесі. In the scientific article, conducted scientific research to legal features of exclusivity of judgments, adopted in special proceeding, entered into legal validity. In particular, it is determined that the exclusivity of judgments, adopted in order to special proceeding is the impossibility of application in the case of special proceeding at the identical requirement. If the requirement for the establishment of a legal fact is disputable, the judgment, adopted in special proceeding, entered into legal validity, will not be an obstacle to the adoption of the statement of claim with the relevant requirement. The legal facts, established by the judgment in special proceeding, which entered into legal validity, shall be recognized as such, which do not require proof in action proceeding. It prejudicial facts, established by such judgments, including facts about the recognition of a person as missing or announcement as deceased, incapacitated or restriction of civil capacity, the resumption of civil capacity, the adoption, establishment of facts of legal significance, is the basis for the committing appropriate actions by state and local authorities, their officials. Selected criteria for the recognition requirement in the case of the establishment of a legal fact in special and action proceedings as identical, that is, one which cannot be re-considered in civil proceedings. In particular, the criterion of identity requirement in special proceeding is the identity of the fact that person seeks to identify, the persons, which related by this fact and the identity of the applicant. At the same time, the presence of the judgment on restrictions on civil capacity does not preclude the filing of a statement of recognition of such person as incapable or of a resumption of civil capacity of a person. The recognition of a person missing does not exclude the adoption of a judgment on the announcement as deceased. The entry of such judgments into legal validity will mean the inability for persons involved in the case, submit an application with identical requirement as long as the judgment entered into legal validity, have not been canceled. In this regard, in the case of occurrence of a person, recognized as missing or declared as dead, and in case of recovery or significant improvement of the mental condition of a person declared incapable or of the disappearance of the grounds for restriction of legal capacity the person whose capacity is limited, it is possible to submit the application for cancellation of such judgment. According to the author, exclusivity is not inherent in a judgment in cases of adoption, due to the inability in practice to establish the identity requirements. In this case, even because of the identity of persons who participated in the case, and a child who is adopted, no identity requirements: causes and reasons for adoption, the circumstances testifying to the conformity of adoption to interests of the child are not identical